Quaternary precipitation strengthening iron-based high-entropy alloy and preparation method thereof

By introducing micro-nano-scale precipitation strengthening technology into iron-based high-entropy alloys, the FCC+B2 structure is formed, and the differences in strong plasticity matching of existing high-entropy alloys are solved, achieving high strength and excellent plastic toughness.

CN119592862APending Publication Date: 2025-03-11CHINA THREE GORGES UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656690.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

There are differences in the strong plasticity matching of existing high-entropy alloys, and it is difficult to improve strength and plasticity at the same time.

Method used

By introducing a strategy to form micro-nano-scale precipitation strengthening, iron-based high-entropy alloys with FCC+B2 structure were prepared. The specific method includes stacking raw materials of Fe, Co, Ni, Al in a specific proportion, performing non-consumable vacuum smelting, followed by solid solution treatment and annealing treatment to form nanoparticles or sheet-like B2 phases distributed on the matrix of the FCC phase.

Benefits of technology

The excellent mechanical properties of high-entropy alloys are achieved, the yield strength reaches 1543.98MPa, the fracture strain is greater than 28.45%, and the high strength and good plastic toughness are also achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592862A_ABST
    Figure CN119592862A_ABST
Patent Text Reader

Abstract

The invention discloses a quaternary precipitation strengthening iron-based high-entropy alloy and a preparation method thereof, the high-entropy alloy comprises the atomic components of Fe, Co, Ni and Al, and the atomic percentage of Fe to Co to Ni to Al is 48%-52%: 23%-27%: 17%-20%: 5%-8%. The preparation process comprises the following steps: preparing four elements of Fe, Co, Ni and Al with the purity higher than 99.95 wt% as alloy elements; the preparation method comprises the following steps: preparing and smelting an as-cast alloy by using a non-consumable vacuum arc melting furnace, then carrying out solid solution treatment by using a heat treatment furnace to obtain a solid solution alloy with a stable single phase, and then carrying out further heat treatment to obtain the high-toughness high-entropy alloy. The high-entropy alloy has fine granular or lamellar B2 phases which are uniformly separated out, precipitates are distributed on a matrix FCC (fluid catalytic cracking) to form precipitation strengthening, and the high-entropy alloy shows excellent comprehensive mechanical properties. Compared with a traditional high-entropy alloy, the high-strength and high-toughness iron-based high-entropy alloy prepared through the method has the excellent comprehensive mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal materials and preparation thereof, and provides a quaternary precipitation-strengthened iron-based high-entropy alloy and a preparation method thereof. Background Art

[0002] In recent years, high entropy alloys (HEAs) have received extensive attention. The main elements and configuration entropies of such alloys are much higher than those of traditional alloys. As a new material proposed in the 21st century, high entropy alloys have broken through the limitations of traditional alloy elements in the past. High entropy alloys are generally composed of five or more metals or non-metals in an equiatomic ratio or a non-equiatomic ratio. Today, the development of high entropy alloys has also expanded to four or more metals or non-metal elements. Compared with traditional alloys, high entropy alloys have four major effects: high entropy effect, lattice distortion effect, retarded diffusion effect and cocktail effect. These four effects give high entropy alloys many excellent properties, such as high strength and hardness, good wear resistance and corrosion resistance. Among them, the lattice distortion effect makes multi-principal element high entropy alloys have higher hardness and good electrical and thermal conductivity, while the retarded diffusion effect can generally improve the thermal stability of the alloy. In addition, scholars use the cocktail effect to change the composition of the alloy and design some high entropy alloys with extremely superior specific properties.

[0003] CoCrFeNi high entropy alloy is one of the earliest high entropy alloys that has been widely studied. This alloy has a single-phase FCC structure and has excellent plasticity at room temperature, but low strength. 2.1 In eutectic high entropy alloys, the FCC phase and the B2 phase can deform synergistically, and the two phases have a KS coherent / semi-coherent orientation relationship. However, the B2 phase in the eutectic high entropy alloy is directly formed in the liquid phase, and the size of the B2 phase is larger than that of solid precipitation. Therefore, we tried to introduce precipitation-strengthened micro-nano particles or lamellar structure B2 phase on the matrix of the FCC phase to obtain high-performance iron-based high entropy alloys.

[0004] Here, for Fe-based high entropy alloys with the composition of FeCoNiAl, we proposed a strategy to obtain high-quality strong high entropy alloys by introducing micro-nanoscale precipitation strengthening. We obtained Fe-based high entropy alloys with nano-precipitation structures by different heat treatment temperatures. The precipitated fine granular or lamellar B2 phases were distributed on the matrix FCC to form precipitation strengthening, which provided the main strengthening effect. This work provides valuable insights for optimizing the high-temperature properties and microstructure design of high-temperature composites to further expand their potential applications in high-temperature fields. Summary of the invention

[0005] Aiming at the problem of poor matching of strength and plasticity of existing high entropy alloys, the present invention provides a quaternary precipitation-strengthened iron-based high entropy alloy and a preparation method thereof. When the raw material components are as follows in atomic molar percentage: Fe: 48%~52%, Co: 23%~27%, Ni: 17%~20%, Al: 5%~8%, the cast alloy is subjected to a solid solution treatment at 1100℃~1200℃ for 6~9h, and then subjected to a heat treatment at 525℃~625℃ for 6~9h, the quaternary precipitation-strengthened iron-based high entropy alloy is an FCC+B2 structure. The high entropy alloy exhibits excellent mechanical properties.

[0006] In order to achieve the purpose of the present invention, the following technical solutions are provided: A quaternary precipitation-strengthened iron-based high-entropy alloy, wherein the raw material components are as follows in atomic molar percentage: Fe: 48%-52%, Co: 23%-27%, Ni: 17%-20%, Al: 5%-8%, the microstructure of the high-entropy alloy is an FCC phase and a B2 phase precipitated and precipitated on a substrate FCC, the FCC phase and the B2 phase are alternately arranged in the structure of the high-entropy alloy, and the B2 phase is in the form of nanoparticles or lamellar layers.

[0007] When the raw material components are as follows in atomic molar percentage: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, the B2 phase is nanoparticle or lamellar, the particle diameter or lamellar size is 90-160nm, the relative content of the B2 phase is 20%-35%, and the further preferred relative content of the B2 phase is 29.6%; the average particle diameter or lamellar width of the B2 phase is 110nm.

[0008] Another object of the present invention is to provide a method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy, wherein the steps of preparing the alloy are as follows: Step (1): Place the raw materials, Al, Ni, Co, Fe in order from bottom to top, on a water-cooled copper crucible, and at the same time place pure titanium for oxygen absorption into another copper crucible; Step (2): using a non-consumable vacuum melting furnace for melting, evacuating the melting furnace twice, aligning the electrode with a copper crucible containing pure Ti, striking an arc and melting to remove residual oxygen, then moving the arc to a high entropy alloy raw material crucible for melting to obtain the cast high entropy alloy; Step (3): heat treatment, subjecting the cast alloy prepared in step (2) to heat treatment, wherein the heat treatment process includes solution treatment and annealing treatment, to obtain a eutectoid high entropy alloy.

[0009] Specifically, in some embodiments, the method further includes raw material preparation, wherein the purity of Ni, Co, Fe and Al raw materials is greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form, the oxide layer is mechanically removed, the selected raw materials are ultrasonically cleaned, and fully dried; the required raw materials Ni, Co, Fe and Al are prepared according to the required quality requirements by converting the mass percentage by molar percentage.

[0010] In some embodiments, during the process of placing the raw materials, the prepared raw materials are stacked in order according to their melting points and placed on water-cooled copper, from bottom to top, namely Al, Ni, Co, and Fe, and pure titanium for oxygen absorption is placed in another copper crucible.

[0011] The smelting furnace was evacuated twice using a mechanical pump and a molecular pump. The first time, the chamber was evacuated to 9.0×10-2Pa ~9.5×10-2 Pa using a mechanical pump, and then argon was filled in to make the vacuum degree in the chamber reach -0.6×105 Pa~-0.5×105Pa; the second time, the chamber was evacuated to 9.0×10-2Pa ~9.5×10-2 Pa using a molecular pump, and then argon was filled in to make the vacuum degree in the chamber reach -0.6×105 Pa~-0.5×105 Pa.

[0012] In some embodiments, the electrode is aligned with a crucible filled with pure Ti, and the electrode is about 3-5 mm away from the pure Ti. After the arc is struck, the melting is performed for 2-3 min to remove residual oxygen, and then the arc is moved to the high entropy alloy raw material crucible for melting.

[0013] During the smelting process in step (2), the arc current intensity is increased from 10-20A to 60-80A slowly, and the smelting is continued for 1-2 minutes. Then the current is increased to 180-200A, and the smelting is continued for 2-3 minutes. Then the current is increased to 320-340A again, and the smelting is continued for 3-4 minutes. After the alloy is completely liquefied, the smelting is continued stably for 3-4 minutes, and the arc is turned off.

[0014] In some embodiments, after the alloy is completely cooled and solidified, it is turned over using a mechanical hook spoon, and the above operation is repeated 5 to 6 times to obtain a cast iron-based high entropy alloy.

[0015] During the solution treatment process in step (3), the temperature is raised to 1100-1200°C at a heating rate of 17-22°C / min, the solution treatment is carried out for 6-9h, and then water cooling is carried out.

[0016] During the annealing treatment in step (3), the temperature is raised to 525-625°C at a heating rate of 9-11°C / min, solution treatment is performed for 6-9h, and then water cooling is performed.

[0017] The present invention has the following beneficial effects: The high entropy alloy prepared by the present invention has excellent plasticity at room temperature, but low strength, based on the design concept of CoCrFeNi high entropy alloy with FCC structure. Therefore, it is intended to introduce micro-nano precipitated particles or lamellar structure B2 phase to optimize the comprehensive performance of the alloy. In eutectic high entropy alloys, if the B2 phase is directly formed in the liquid phase, the size of the B2 phase is larger than that of solid precipitation. Therefore, after reasonable composition adjustment and heat treatment, we successfully prepared a quaternary precipitation-strengthened iron-based high entropy alloy, which formed precipitation-strengthened micro-nano particles or lamellar structure B2 phase on the matrix of the FCC phase, and obtained a high-performance iron-based high entropy alloy.

[0018] The present invention provides a quaternary precipitation-strengthened iron-based high-entropy alloy, which has precipitation strengthening and improved performance. The precipitation-strengthened high-entropy alloy obtained by heat treatment in the temperature range of 525°C to 625°C has fine granular or lamellar B2 phases uniformly precipitated and distributed on the matrix FCC. Compared with the high-entropy alloy obtained by heat treatment at low temperature (500°C), the strength and plasticity are significantly improved; compared with the high-entropy alloy obtained by heat treatment at high temperature (650°C), the alloy strength is lower but the plasticity is greatly improved. The yield strength of the high-entropy alloy is greater than or equal to 1543.98MPa, and the fracture strain is greater than or equal to 28.45%. It has high strength and exhibits excellent plasticity and toughness, and its comprehensive performance is relatively excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is an experimental flow chart in a specific implementation manner of the present invention.

[0020] Figure 2 It is the XRD spectrum of the high entropy alloy in the specific embodiment of the present invention.

[0021] Figure 3 1 is a room temperature compressive stress-strain curve of a high entropy alloy in a specific embodiment of the present invention.

[0022] Figure 4 is a metallographic diagram of a high entropy alloy in a specific embodiment of the invention, wherein (A) is Fe obtained in Example 1 50 Co 25 Ni 18.5 Al 6.5 Metallographic diagram; (B) is the Fe obtained in Example 2 50 Co 25 Ni 18.5 Al 6.5 Metallographic diagram; (C) Fe obtained in Comparative Example 1 50 Co 25 Ni 18.5 Al 6.5 Metallographic diagram; (D) is the Fe obtained in Comparative Example 250 Co 25 Ni 18.5 Al 6.5 Metallographic diagram; (E) is the Fe obtained in Comparative Example 4 50 Co 25 Ni 18.5 Al 6.5 Metallographic diagram. DETAILED DESCRIPTION

[0023] The microstructure characterization and mechanical property test information of the high entropy alloy are as follows: (1) Phase analysis: X-ray diffraction analysis was performed using an Ultima IV Cu Kα diffractometer (λ = 1.54Å). The operating voltage and current were 40KV and 40mA, respectively. The 2θ scanning range was from 20° to 100° at a speed of 4° / min. The results are shown in Figure 1 .

[0024] (2) Mechanical properties: According to the relevant requirements of GB / T 7314-2017 Metal Material Room Temperature Compression Test Method, a room temperature compression test was carried out, and the experimental compression loading rate was 0.36 mm / min. Two experiments were carried out for each component alloy, and the stress-strain curve data was the average of the two times. The results are as follows Figure 2 .

[0025] (3) Microstructure: The sample was observed under a scanning electron microscope at different magnifications. Figure 3 .

[0026] In order to facilitate a comprehensive understanding of the specific implementation of the present invention, the present invention will be described in detail below in conjunction with specific embodiments and drawings, as well as preferred embodiments. It should be emphasized that the protection scope of the present invention is not limited to the following specific embodiments.

[0027] All professional terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0028] In the present invention, various raw materials, reagents, instruments and equipment used can be obtained through conventional channels without the need for special procurement channels or specific supply chains.

[0029] The present invention will be further described below in conjunction with specific embodiments.

[0030] Example 1 A quaternary precipitation-strengthened iron-based high entropy alloy An iron-based high entropy alloy of the present invention, the molar percentages of the alloy elements are as follows: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the raw materials of Ni, Co, Fe and Al with a purity greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form; mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0031] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Step (8): heat treatment, the cast alloy prepared in step (7) is heat treated, the heat treatment process is solution treatment and heat treatment, the solution treatment temperature is 1150°C and the solution treatment time is 8 hours, the solution treatment heating rate is 20°C / min, the heat treatment temperature is 600°C and the heat treatment time is 8 hours, the heat treatment heating rate is 10°C / min, the solution treatment and heat treatment are both carried out in a box-type heat treatment furnace and cooled by water cooling, to obtain a quaternary precipitation-strengthened iron-based high entropy alloy; For the Fe 50 Co 25 Ni 18.5 Al6.5 The high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum was as follows: Figure 2 As shown in the figure, Fe 50 Co 25 Ni 18.5 Al 6.5 The alloy has a FCC+B2 structure.

[0032] For Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure of the high entropy alloy sample was analyzed, and the scanning electron microscope (SEM) photos were as follows: Figure 4 (A), from the analysis of the figure, we can see that the high entropy alloy Fe 50 Co 25 Ni 18.5 Al 6.5 The structure is composed of FCC phase and B2 phase which is precipitated and distributed on the base FCC in the form of nanoparticles or lamellar. The structure is composed of alternating arrangement of partly lamellar FCC phase and B2 phase, and partly B2 phase which is precipitated and distributed on the base of FCC in the form of nanoparticles. The thickness of B2 lamellar layer or the diameter of nanoparticle is about 110nm, and the content of B2 phase is 29.6%.

[0033] For Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is as follows Figure 3 As shown, it can be seen that Fe 50 Co 25 Ni 18.5 Al 6.5 The alloy has a yield strength of 1543.98 MPa, a compressive strength of 2932.11 MPa, and a fracture strain of 40.72%. It has high strength and exhibits good plasticity and toughness.

[0034] Example 2 A quaternary precipitation-strengthened iron-based high entropy alloy An iron-based high entropy alloy of the present invention, the molar percentages of the alloy elements are as follows: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the raw materials of Ni, Co, Fe and Al with a purity greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form; mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0035] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Step (8): heat treatment, the cast alloy prepared in step (7) is heat treated, the heat treatment process is solution treatment and heat treatment, the solution treatment temperature is 1150°C and the solution treatment time is 8 hours, the solution treatment heating rate is 20°C / min, the heat treatment temperature is 550°C and the heat treatment time is 8 hours, the heat treatment heating rate is 10°C / min, the solution treatment and heat treatment are both carried out in a box-type heat treatment furnace and cooled by water cooling, to obtain a quaternary precipitation-strengthened iron-based high entropy alloy; For the Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum was as follows: Figure 2 As shown in the figure, Fe 50 Co 25 Ni18.5 Al 6.5 , the alloy has a FCC+B2 phase structure.

[0036] For Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure of the high entropy alloy samples was analyzed, and the scanning electron microscope (SEM) photos were shown in Figure 4 (B), from the analysis of the figure, we can see that the high entropy alloy Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure is composed of FCC phase and B2 phase which is precipitated and deposited on the base FCC in intermittent lamellar or nano-granular form. The thickness of B2 lamellar or the diameter of nano-granular is about 100nm, and the content of B2 phase is 23.4%.

[0037] For Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is as follows Figure 3 As shown, it can be seen that Fe 50 Co 25 Ni 18.5 Al 6.5 The alloy has a yield strength of 1786.71MPa, a compressive strength of 2786.14MPa, and a fracture strain of 28.45%. It has high strength and exhibits good plasticity and toughness.

[0038] Comparative Example 1 A quaternary precipitation-strengthened iron-based high entropy alloy An iron-based high entropy alloy of the present invention, the molar percentages of the alloy elements are as follows: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the raw materials of Ni, Co, Fe and Al with a purity greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form; mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0039] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Step (8): heat treatment, the cast alloy prepared in step (7) is heat treated, the heat treatment process is solution treatment and heat treatment, the solution treatment temperature is 1150°C and the solution treatment time is 8 hours, the solution treatment heating rate is 20°C / min, the heat treatment temperature is 650°C and the heat treatment time is 8 hours, the heat treatment heating rate is 10°C / min, the solution treatment and heat treatment are both carried out in a box-type heat treatment furnace and cooled by water cooling, to obtain a quaternary precipitation-strengthened iron-based high entropy alloy; For the Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum was as follows: Figure 2 As shown in the figure, Fe 50 Co 25 Ni 18.5 Al 6.5 , the alloy has a FCC+B2 phase structure.

[0040] For Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure of the high entropy alloy samples was analyzed, and the scanning electron microscope (SEM) photos were shown in Figure 4 (C), from the analysis of the figure, we can see that the high entropy alloy Fe 50 Co 25 Ni 18.5 Al 6.5 The structure is composed of FCC phase and B2 phase which is precipitated and deposited on the base FCC in the form of nanoparticles. The structure is composed of FCC phase and lamellar or granular B2 phase, in which the lamellar thickness or particle diameter of B2 phase reaches 500nm, and the content of B2 phase is 36.1%.

[0041] For Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is as follows Figure 3 As shown, it can be seen that Fe 50 Co 25 Ni 18.5 Al 6.5 The yield strength of the alloy is 2050.27MPa, the compressive strength is 2951.06MPa, and the fracture strain is 18.70%. Compared with the precipitation-strengthened high-entropy alloy obtained by heat treatment in the temperature range of 525℃~625℃, although the strength is slightly improved, the plastic toughness is greatly reduced.

[0042] Comparative Example 2 A quaternary precipitation-strengthened iron-based high entropy alloy An iron-based high entropy alloy of the present invention, the molar percentages of the alloy elements are as follows: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the raw materials of Ni, Co, Fe and Al with a purity greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form; mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0043] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Step (8): heat treatment, the cast alloy prepared in step (7) is heat treated, the heat treatment process is solution treatment and heat treatment, the solution treatment temperature is 1150°C and the solution treatment time is 8 hours, the solution treatment heating rate is 20°C / min, the heat treatment temperature is 500°C and the heat treatment time is 8 hours, the heat treatment heating rate is 10°C / min, the solution treatment and heat treatment are both carried out in a box-type heat treatment furnace and cooled by water cooling, to obtain a quaternary precipitation-strengthened iron-based high entropy alloy; For the Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to phase analysis, and its X-ray diffraction (XRD) spectrum was as follows: Figure 2 As shown in the figure, Fe 50 Co 25 Ni 18.5 Al 6.5 , the alloy has a FCC+B2 phase structure.

[0044] For Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure of the high entropy alloy samples was analyzed, and the scanning electron microscope (SEM) photos were shown in Figure 4 (D), from the analysis of the figure, we can see that the high entropy alloy Fe 50 Co 25 Ni 18.5 Al 6.5The microstructure is FCC phase and B2 phase which is precipitated in the form of nanoparticles and deposited on the base FCC. The content of B2 phase is 15.3% and the average diameter of the nanoparticles is 89nm.

[0045] For Fe 50 Co 25 Ni 18.5 Al 6.5 The high entropy alloy sample was subjected to room temperature compression test, and its compression true stress-strain curve is as follows Figure 3 As shown, it can be seen that Fe 50 Co 25 Ni 18.5 Al 6.5 The yield strength of the alloy is 845.26MPa, and it does not break under compression. Compared with the precipitation-strengthened high-entropy alloy obtained by heat treatment in the temperature range of 525℃~625℃, it has better plasticity and toughness, but lower strength.

[0046] Comparative Example 3 An iron-based high entropy alloy, the molar percentages of the alloy elements are as follows: Ni: 25%, Co: 5%, Cr: 5%, Fe: 55%, Al: 10%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the purity of Ni, Co, Cr, Fe and Al raw materials greater than 99.98% (wt); mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and using an electronic scale to prepare the required raw materials Ni, Co, Cr, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe and Cr from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0047] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Fe 55 Co 20 Ni 15 Al 10 , FCC+B2 structure, direct eutectic B2 phase with a size of more than ten microns in the liquid phase, yield strength of 1450MPa, and fracture strain of 29%.

[0048] Comparative Example 4 A quaternary precipitation-strengthened iron-based high entropy alloy An iron-based high entropy alloy of the present invention, the molar percentages of the alloy elements are as follows: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, and the specific preparation method is as follows: Step (1): pre-treating the raw materials, selecting the raw materials of Ni, Co, Fe and Al with a purity greater than 99.98% (wt); wherein Fe and Ni are in granular form, and Co and Al are in block form; mechanically removing the oxide layer, ultrasonically cleaning the selected raw materials, and fully drying; Step (2): preparing raw materials, converting the molar percentage into the mass percentage, and preparing the required raw materials Ni, Co, Fe and Al according to the required mass; Step (3): placing the raw materials. The raw materials prepared in step (2) are stacked in order of melting point in a water-cooled copper crucible, i.e., Al, Ni, Co, Fe from bottom to top. At the same time, pure titanium used for oxygen measurement and oxygen absorption is placed in another copper crucible.

[0049] Step (4): Primary vacuum: Use a mechanical pump to perform the initial vacuum treatment, and evacuate the chamber to 9.5×10 -2 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (5): Secondary vacuum: Use a molecular pump to perform secondary vacuum treatment, and evacuate the chamber to 9.5×10 -3 After that, argon gas was filled into the chamber to make the vacuum degree in the chamber reach -0.5×10 5 Pa; Step (6): smelting pretreatment, before starting smelting, adjust the welding gun to the copper crucible containing pure titanium, strike an arc to melt the pure titanium and eliminate residual oxygen; Step (7): start smelting, adjust the welding gun to the copper crucible containing the alloy to start the arc, and slowly increase the arc current from 10~20A to 320~340A. First, set the current intensity to 10~20A, then slowly increase the current to 60~80A, and smelt for 1~2min. Then increase the current to 180~200A, and smelt for 2~3min. Increase the current to 320~340A again, and smelt for 3~4min. After the alloy is completely liquefied, stably melt for 3~4min, and turn off the arc. After the alloy is completely cooled and solidified, turn it over with a mechanical hook spoon, and repeat the above operation 5~6 times to obtain a cast iron-based high entropy alloy. Step (8): heat treatment, heat treatment of the cast alloy prepared in step (7), the heat treatment process is solution treatment and heat treatment, the solution treatment temperature is 1050°C and the solution treatment time is 6 hours, the solution treatment heating rate is 20°C / min, the heat treatment temperature is 600°C and the heat treatment time is 6 hours, the heat treatment heating rate is 10°C / min, the solution treatment and heat treatment are both carried out in a box-type heat treatment furnace and cooled by water cooling, to obtain a quaternary precipitation-strengthened iron-based high entropy alloy; For Fe 50 Co 25 Ni 18.5 Al 6.5 , the microstructure of the high entropy alloy sample was analyzed, and the metallographic microscope photos were as follows Figure 4 (E), from the analysis of the figure, we can see that the high entropy alloy Fe 50 Co 25 Ni 18.5 Al 6.5 The microstructure is FCC phase and B2 phase precipitated in coarse lamellar form with a size of tens of microns.

[0050] Table 1 is a comparison of the yield strength and fracture strain of Examples 1-2 and Comparative Examples 1-3.

[0051]

[0052] like Figure 3As shown in Table 1, by comparing Example 2 and Comparative Example 2, the 550°C heat-treated alloy has achieved a significant improvement in strength relative to the low-temperature (500°C) heat-treated alloy, and the yield strength of the alloy has increased from 845.26MPa to 1786.71MPa. This is mainly due to the increase in the amount of B2 phases of nanoparticles or lamellar structures uniformly precipitated on the matrix of the FCC phase as the heat treatment temperature increases, and the precipitation strengthening effect is enhanced, thereby improving the strength of the alloy. By comparing Example 1 and Comparative Example 1, the 600°C heat-treated alloy has a slight decrease in strength relative to the high-temperature (650°C) heat-treated alloy, while its plasticity has been improved. This is mainly because when the alloy is treated at high temperature, the size of the B2 phases of nanoparticles or lamellar structures uniformly precipitated on the matrix of the FCC phase of the alloy becomes coarse. By comparing Example 1 and Comparative Example 3, the cast Fe 55 Ni 25 Co5Cr5Al 10 The liquid phase of the alloy will directly eutectic B2 phase with a size of more than ten microns. Compared with the 600℃ heat-treated alloy with FCC phase and B2 phase uniformly precipitated on the matrix of FCC phase in the form of nanoparticles or lamellar structures, the coarse B2 phase precipitated in the cast Fe 55 Ni 25 Co5Cr5Al 10 The mechanical properties of the alloy are poor. By comparing Example 1 and Comparative Example 4, due to the differences in solution temperature, heat treatment temperature and holding time, the B2 phase in the alloy treated at 1050°C for 6h and 600°C for 6h is precipitated in the form of coarse particles or lamellae, and it is impossible to obtain a B2 phase structure uniformly precipitated on the matrix of the FCC phase in the form of nanoparticles or lamellae, and the mechanical properties are poor. In addition, Example 1 exhibits excellent comprehensive mechanical properties, and its alloy yield strength, compressive strength and fracture strain are as high as 1543.98MPa, 2932.11MPa and 40.72%, respectively.

[0053] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which are all within the protection scope of the present invention.

Claims

1. A quaternary precipitation-strengthened iron-based high entropy alloy, characterized in that: The raw material components are as follows in atomic molar percentage: Fe: 48%~52%, Co: 23%~27%, Ni: 17%~20%, Al: 5%~8%. The microstructure of the high entropy alloy is FCC phase and B2 phase precipitated and deposited on the substrate FCC. The FCC phase and B2 phase are arranged alternately in the structure of the high entropy alloy. The B2 phase is nanoparticle or lamellar, with a particle diameter or lamellar size of 90-160nm, and the content of B2 phase is 20%-35%.

2. The quaternary precipitation-strengthened iron-based high entropy alloy according to claim 1, characterized in that: When the raw material components are as follows by atomic mole percentage: Fe: 50%, Co: 25%, Ni: 18.5%, Al: 6.5%, the relative content of B2 phase is 29.6%; the average particle diameter or lamellar width of B2 phase is 110nm.

3. The method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy according to claims 2 and 3, characterized in that: The alloy preparation steps are as follows: Step (1): Place the raw materials, Al, Ni, Co, Fe in order from bottom to top, on a water-cooled copper crucible, and at the same time place pure titanium for oxygen absorption into another copper crucible; Step (2): using a non-consumable vacuum melting furnace for melting, evacuating the melting furnace twice, aligning the electrode with a copper crucible containing pure Ti, striking an arc and melting to remove residual oxygen, then moving the arc to a high entropy alloy raw material crucible for melting to obtain the cast high entropy alloy; Step (3): heat treatment, subjecting the cast alloy prepared in step (2) to heat treatment, wherein the heat treatment process includes solution treatment and annealing treatment, to obtain a eutectoid high entropy alloy.

4. The method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy according to claim 3, characterized in that: In step (2), the vacuum is first drawn to 9.0 × 10 -2 Pa~9.5×10 -2 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 Pa; then further evacuate the furnace with a molecular pump to a pressure of 9.0×10 -2 Pa~9.5×10 -2 Pa, and then filled with argon to -0.6×10 5 Pa~-0.5×10 5 MPa.

5. The method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy according to claim 4, characterized in that: During the smelting process in step (2), the arc current intensity is increased from 10-20A to 60-80A slowly, and the smelting is continued for 1-2 minutes. Then the current is increased to 180-200A, and the smelting is continued for 2-3 minutes. Then the current is increased to 320-340A again, and the smelting is continued for 3-4 minutes. After the alloy is completely liquefied, the smelting is continued stably for 3-4 minutes, and the arc is turned off.

6. The method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy according to claim 3, characterized in that: During the solution treatment process in step (3), the temperature is raised to 1100-1200°C at a heating rate of 17-22°C / min, the solution treatment is carried out for 6-9h, and then water cooling is carried out.

7. The method for preparing a quaternary precipitation-strengthened iron-based high entropy alloy according to claim 6, characterized in that: During the annealing treatment in step (3), the temperature is raised to 525-625°C at a heating rate of 9-11°C / min, solution treatment is performed for 6-9h, and then water cooling is performed.